Digital Competences in The Soft Skills of Primary Level Teachers - Zuñiga, Vanessa del Pilar Pacheco; Pinargote, Fabricio Daniel Saltos; Álvarez, Tania Elizabeth Vásquez; Alvarez, Maritza YeleneVásquez (International Journal of Membrane Science and Technology, 2023)
The research, as a result of the thesis degree, was developed in order to present a proposal that allows strengthening the digital skills in the soft skills of teachers at the primary level of the Pacaipampa district of Piura-Peru. It is based on the theories of cognitivism, constructivism and connectivism, so that teachers learn new strategies and techniques, and how to apply them in the teaching and learning processes of the students of the educational institutions of the aforementioned district, in an active, motivating and autonomous during their academic phase. The applied methodology is of a basic type, propositional descriptive level, with a quantitative approach, with the total population of 100 teachers participating in the survey, applying two questionnaires with their respective validation. The Excel tool was used to tabulate the results, in which was detected that in digital skills, the category with the highest percentage in 4 of the 5 dimensions is sometimes, while in soft skills "almost always" predominates in 3 of the 5 dimensions. This indicates that both skills should be reinforced in teachers in an articulated way with innovative strategies. The final product was the preparation and presentation of a proposal for activities and implementation phases that strengthen training in the skills of the two variables, thereby facilitating the updating of teaching while optimizing teaching-learning processes, facing the challenges of the digital society and fully train students with the skills demanded in the 21st century.